PERLINDUNGAN KONSUMEN TERHADAP PRODUK KADALUWARSA (STUDI PERBANDINGAN HUKUM PERLINDUNGAN KONSUMEN INDONESIA DAN MALAYSIA) - Walangitang, Alicia Valda Veyfra (Universitas Ekasakti, 2023)
In buying and selling activities, business actors as product providers try to avoid losses as much as possible. Not a few frauds are committed by business actors who sell expired products that are detrimental to consumers. Consumer protection is urgently needed given the weaker position of the consumer. Indonesia and Malaysia as ASEAN members regulate consumer protection. Indonesia established Law No. 8 of 1999 concerning Consumer Protection and Malaysia holds Consumer Protection in the 1999 Consumer Protection Act (CPA). The problem formulation of this writing is to discuss the regulatory provisions regarding expired products and the perpetrators are responsible for losses due to expired products in Indonesia and Malaysia. In this paper the research method is normative legal research. The approach in this paper is the statutory approach and the comparative approach. The conclusion of this paper is that the provisions of Indonesian and Malaysian consumer protection laws both regulate business actors who are prohibited from trading expired products and require business actors to put information labels or explanations including the expiration date of a product. For the responsibility of business actors, Indonesia and Malaysia apply reverse verification in the Consumer Protection Law.